Biofunctionalized quantum dots for live monitoring of stem cells: applications in regenerative medicine. (May 2012) - de Mel, Achala; Oh, Jung-Taek; Ramesh, Bala; Seifalian, Alexander M
Aim: This study aimed to live monitor the degree of endothelial progenitor cell (EPC) integration onto tissue-engineering scaffolds by conjugating relevant antibodies to quantum dots (QDs).Materials & methods: Biocompatible mercaptosuccinic acid-coated QDs were functionalized with two different antibodies to EPC (CD133 with QDs of 640 nm wavelength [λ] and later-stage mature EPCs; and von Willebrand factor with QDs of λ595 and λ555 nm) using conventional carbomide and N-hydroxysuccinimide chemistry. Biofunctionalization was characterized with Fourier-transform infrared spectroscopy. Cell viability assays and gross morphology observations confirmed cytocompatibility and normal patterns of celluar growth. The antigens corresponding to each state of cell maturation were determined using a single excitation at λ488 nm.Results: The optimal concentrations of antibody–QD conjugates were biocompatible, hemocompatible and determined the state of EPC transformation to endothelial cells.Conclusion: Antibody-functionalized QDs suggest new applications in tissue engineering of polymer-based implants where cell integration can potentially be monitored without requiring the sacrifice of implants.